Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Combinatorial approach through in vitro regeneration and phytochemical profiling of ceropegia media (huber) ans.: a potential way forward in the conservation of an endangered medicinal plant from the western ghats in India - Pandey, Meena; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Giri, Ashok P. (Journal of Plant Growth Regulation, 2020)
Ceropegia mediais an endemic and endangered plant as its propagation through seeds is unreliable due to low germination, slow growth and seedling decay under natural conditions. Also, tubers of this plant are edible serving as carbohydrate source with medicinal values leading to severe population decline in the natural habitat. To provide a sustainable solution, an efficient in vitro propagation protocol along with phytochemical profiling was developed forC. media. Callus cultures were induced from seedling and wild leaf tissues using the most effective Murashige and Skoog's (MS) medium with 2,4-dichlorophenoxyacetic acid (2,4-D; 2 mu M) and sucrose (3%). Somatic embryos were acquired on MS medium with 1 mu M 6-Benzylaminopurine (BAP) and 1 mu M 2,4-D. Conversion into plantlets was attained only from tissue culture-derived seedling leaf (TCDSL) explant. Further, in vitro tuberization was achieved from TCDSL callus with BAP and Naphthalene acetic acid (NAA). AgNO(3)as an elicitor had a positive effect on both fresh and dry weights of callus. Successful acclimatization (58%) was attained after two months resulting in normal phenotype in pots. Further, metabolite profiles of ten different tissues from wild and in vitro plants were compared. Total 82 compounds comprising alkaloids, fatty acids, fatty acid ester, steroids, terpenes and hydrocarbons were identified. Overall, results suggested enhanced production of selected metabolites with in vitro propagation and AgNO3, alleviating the problem of unavailability of planting materials. Thus, the current study might offer potential ways for the conservation of such RED enlisted species asC. media. [GRAHICS]
Keywords: Ceropegia media; GC-MS; Microtuberization; Secondary metabolites; Silver nitrate; somatic embryogenesis

Generation of novelties in the genus Ocimum as a result of natural hybridization: a morphological, genetical and chemical appraisal - Gurav, Tanuja P.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Dholakia, Bhushan B.; Giri, Ashok P. (Industrial Crops and Products, 2020)
The genus Ocimum is a boutique of a diverse set of specialized metabolites such as terpenoids and phenylpropanoids. Each Ocimum species and its cultivars represent a characteristic chemical profile. The present study explored the two interspecific Ocimum hybrids originating through a serendipitous natural cross between O. kilimandscharicum and O. basilicum. These two novel Ocimum hybrids exhibited intermediate morphological features of two parental species. Inter simple sequence repeats (ISSR) analysis and DNA barcoding with the plastid non-coding trnH-psbA intergenic spacer region reaffirmed unambiguous parental identification and differentiation of these natural hybrids from other available Ocimum species. Consequently, gas chromatographymass spectrometry-based metabolite profiling of two hybrids identified them as specific chemotypes with the presence of a unique blend of specialized metabolites from the parental species, which are either rich in terpenes or phenylpropanoids. Additionally, expression analysis of key genes from terpenoid and phenylpropanoid pathways corroborated with differential metabolite accumulation. Thus, these two Ocimum hybrids represented the novel chemotypes, which could be useful in commercial cultivation to produce novel essential oil and bioactive constituents. Further, the resulting metabolite diversity could have potential industrial applications in the areas of healthcare, bioremediation, and crop protection.
Keywords: Chemotype; DNA barcoding; Inter Simple Sequence Repeats; Interspecific hybrid; O. basilicum; O. kilimandscharicum; Ocimum

High-throughput metabolomic and transcriptomic analyses vet the potential route of cerpegin biosynthesis in two varieties of Ceropegia bulbosa Roxb. - Gharat, Sachin A.; Shinde, Balkrishna A.; Mule, Ravindra D.; Punekar, Sachin A.; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Ramaswamy, Gopalakrishna; Giri, Ashok P. (Planta, 2020)
Ceropegia bulbosa is an important medicinal plant, used in the treatment of various ailments including diarrhea, dysentery, and syphilis. This is primarily attributed to the presence of pharmaceutically active secondary metabolites, especially cerpegin. As this plant belongs to an endemic threatened category, genomic resources are not available hampering exploration on the molecular basis of cerpegin accumulation till now. Therefore, we undertook high-throughput metabolomic and transcriptomic analyses using different tissues from two varieties namely, C. bulbosa var. bulbosa and C. bulbosa var. lushii. Metabolomic analysis revealed spatial and differential accumulation of various metabolites. We chemically synthesized and characterized the cerpegin and its derivatives by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Importantly, these comparisons suggested the presence of cerpegin and 5-allyl cerpegin in all C. bulbosa tissues. Further, de novo transcriptome analysis indicated the presence of significant transcripts for secondary metabolic pathways through the Kyoto encyclopedia of genes and genomes database. Tissue-specific profiling of transcripts and metabolites showed a significant correlation, suggesting the intricate mechanism of cerpegin biosynthesis. The expression of potential candidate genes from the proposed cerpegin biosynthetic pathway was further validated by qRT-PCR and NanoString nCounter. Overall, our findings propose a potential route of cerpegin biosynthesis. Identified transcripts and metabolites have built a foundation as new molecular resources that could facilitate future research on biosynthesis, regulation, and engineering of cerpegin or other important metabolites in such non-model plants.
Keywords: 5-Allyl cerpegin; Ceropegia; Cerpegin; LC-MS; metabolite; Transcriptome

Genomic determinants of entomopathogenic fungi and their involvement in pathogenesis - Vidhate, Ravindra P.; Dawkar, Vishal V.; Punekar, Sachin A.; Giri, Ashok P. (Microbial Ecology, 2023)
Entomopathogenic fungi offer an effective and eco-friendly alternative to curb insect populations in biocontrol strategy. The evolutionary history of selected entomopathogenic fungi indicates their ancestral relationship with plant endophytes. During this host shifting, entomopathogenic fungi must have acquired multiple mechanisms, including a combination of various biomolecules that make them distinguishable from other fungi. In this review, we focus on understanding various biochemical and molecular mechanisms involved in entomopathogenesis. In particular, we attempt to explain the indispensable role of enlarged gene families of various virulent factors, viz. chitinases, proteases, lipases, specialized metabolites, and cytochrome P450, in entomopathogenesis. Our analysis suggests that entomopathogenic fungi recruit a different set of gene products during the progression of pathogenesis. Knowledge of these bio-molecular interactions between fungi and insect hosts will allow researchers to execute pointed efforts towards the development of improved entomopathogenic fungal strains.
Keywords: Biocontrol; Chitinases; Endophytic fungi; Entomopathogenic fungi; Hydrolytic enzymes; Insect pests

Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization